Konsep Sendiko Dawuh di Pondok Pesantren Ma'hadut Tholabah Kabupaten Tegal - Alif Muzaki; Aris Munandar; Moh. Sihabudin; Nur Fadilah Fitri (La-Tahzan: Jurnal Pendidikan Islam, 2023)
In Javanese, sendiko means "I obey" or "according to", while dawuh can be interpreted as telling someone else to do an order. So, the meaning of sendiko dawuh is to obey or comply with orders from people who are respected because of their rank or knowledge. This research aims to: 1. Explaining the concept of sendiko dawuh in Ma'hadut Tholabah boarding school.  2. Explaining how to solve problems about sendiko dawuh. This research is an explanatory descriptive research with the method of presenting data, namely the method of listening (observation). Listening and observation here are carried out with the technique of simak bebas libat cakap (SBLC). Then the data is analyzed using qualitative methods with interview techniques. The results of data analysis are presented formally and informally. The results of the research show that there are various concepts of sendiko dawuh. Sendiko dawuh is not only to kyai, but also to people we respect such as parents, teachers, etc.